Clinical Use of Peptide-Based Formula (Peptamen Junior®, Nestle) in the Paediatric Population - Ford, Kristyn; Gilbertson, Heather (International Journal of Nutrition, 2022)
Aim There is limited published data describing the characteristics of the paediatric population prescribed semi elemental formulas. This retrospective observational audit aimed to describe the characteristics of the paediatric patients who have been prescribed a hydrolysed whey protein, medium chain triglycerides (MCT) based formula, Peptamen Junior® and the nutritional outcomes. Methods A retrospective observation audit was completed on a cohort of patients that was prescribed a semi elemental formula between 2016 and 2019 from a single tertiary paediatric medical centre. Data variables were collated such as patient characteristics, indications and modalities of administration, duration and tolerance to the formula. Results Data was collated on 375 patients with a median age of 6.2 years. The main underlying medical conditions were haematological/oncology (67%), gastrointestinal disorders (10.7%) and neurological conditions (9.4%). The most common indications for use were chemotherapy related side effects (36.2%), post bone marrow transplant (25.8%) and gastrointestinal symptoms (17.9%). The formula was rarely used as a sole source of nutrition, with 88% patients requiring accompanying forms of nutrition support. The majority of orders prescribed were of standard concentration (80.8%) and tolerance was recorded in 82.8% of patients. Conclusion The semi elemental formula Peptamen Junior® appears to be well tolerated in paediatric patients with a variety of medical conditions that have complex pathologies and may have wider scope of use in a more diverse group of medical conditions than currently indicated.
Keywords: Enteral Nutrition; Food Formulated; Paediatrics; Malabsorption; Malnutrition